Percutaneous Valvuloplasty for Bioprosthetic Tricuspid Valve Stenosis - Rana, Gaurav (Tex Heart Inst J, 2017)
Percutaneous transcatheter tricuspid balloon valvuloplasty (PTTBV) is an accepted treatment option for symptomatic severe native tricuspid valve stenosis, although surgical tricuspid valve replacement remains the treatment of choice. There have been few reports of successful PTTBV for bioprosthetic tricuspid valve stenosis. We present case reports of 3 patients from our hospital experience. Two of the 3 cases were successful, with lasting clinical improvement, whereas the 3rd patient failed to show a reduction in valve gradient. We describe the standard technique used for PTTBV. We present results from a literature review that identified 16 previously reported cases of PTTBV for bioprosthetic severe tricuspid stenosis, with overall favorable results. We conclude that PTTBV should perhaps be considered for a select patient population in which symptomatic improvement and hemodynamic stability are desired immediately, and particularly for patients who are inoperable or at high surgical risk.